2011
DOI: 10.4187/respcare.00915
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Differences Between COPD Exacerbation and Community-Acquired Pneumonia

Abstract: OBJECTIVE: To study the differences in pathogen distribution and antibiotic susceptibility between patients with COPD exacerbation and patients with community-acquired pneumonia, and develop guidance for antibiotic treatment of those conditions. METHODS: We retrospectively analyzed the medical records of 586 COPD-exacerbation patients and 345 community-acquiredpneumonia patients from January 2007 to December 2008, including sputum culture results, antibiotic susceptibilities of the microorganisms, and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
6
30
0
1
Order By: Relevance
“…This isolation rate is in accordance with previous studies reporting an isolation rate of 32 % to 51 % performed in similar settings [16][17][18][19]. Our results demonstrated a predominance of P. aeruginosa, S. pneumonia, H. influenzae, and A. baumanii as the most common sputum isolates in AECOPD patients requiring hospitalization.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This isolation rate is in accordance with previous studies reporting an isolation rate of 32 % to 51 % performed in similar settings [16][17][18][19]. Our results demonstrated a predominance of P. aeruginosa, S. pneumonia, H. influenzae, and A. baumanii as the most common sputum isolates in AECOPD patients requiring hospitalization.…”
Section: Discussionsupporting
confidence: 82%
“…isolates in respiratory samples of COPD patients with severe exacerbations. Previous studies have demonstrated a significant variation in the relative incidence of specific pathogens in AECOPD, which may relate to patient inclusion criteria, settings and environmental or epidemiological factors [10,[19][20][21][22]. Nearly 15% of our study group had at least two prior admissions in the previous year before enrollment into this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P. aeruginosa rarely causes community-acquired pneumonia, there have been high morbidity and mortality rates amongst high-risk patients, including those who are w62 years old or immunocompromised with pre-existing conditions, such as human immunodeficiency virus infection, diabetes mellitus, renal failure, burns, chronic obstructive pulmonary disease, smoker or congestive heart failure (Jorgensen & Ferraro, 2009;Li et al, 2011;Shah et al, 2010). In addition, P. aeruginosa has increased resistance to many antibiotics due to several adaptations, which include membrane impermeability, efflux pumps, biofilm formation and enzyme expression (Henwood et al, 2001;Landman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Although the effect of colonized bacteria on acute exacerbations is not yet clear, more recently, in the relationship between acute exacerbation and increased bacterial burden, the proliferation of new strains has been suggested. [17][18] From studies evaluating the parameters associated with bacterial colonization, a significant relationship was found between the frequency of exacerbations and increased colonization. 14,19 There are studies showing correlation between the decrease in FEV1 and the colonization.…”
Section: Etıology Of Exacerbatıonsmentioning
confidence: 99%